Synopsis and typification of the names published by Antonio Bertoloni in Florula Guatimalensis and in preceding publications - Baldini, Riccardo M.; Macvean, Ana Lucrecia; Cristofolini, Giovanni; Daniel, Thomas F.; Managlia, Annalisa; Galloni, Marta (Phytotaxa, 2019)
Bertoloni published Florula guatimalensis in 1840, which is commonly cited as the original publication. However, our findings show that previous publications of Alessandrini of 1838 and 1840 include the original descriptions by Bertoloni which predate Florula guatimalensis. Among the 60 new taxa authored by Bertoloni, 26 were published in 1838 and 34 in 1840 by Alessandrini. Additionally, original drawings were discovered inside an old copy of Bertoloni’s Florula guatimalensis. Also a comparison between the original material from Bertoloni’s herbarium and his original drawings is here reported for the first time. The collection of Guatemalan plants studied by Antonio Bertoloni preserved at BOLO was analysed and is here discussed. The new combinations Odontonema corymbulosum and Lamourouxia barbata are proposed. A neotype for Aristolochia podocarpa and an epitype for Philadelphus myrtoides are here designated.